Blood Hemoglobin, in-vivo Alzheimer Pathologies, and Cognitive Impairment: A Cross-Sectional Study - Kim, Jee Wook; Byun, Min Soo; Yi, Dahyun; Lee, Jun Ho; Jeon, So Yeon; Ko, Kang; Joung, Haejung; Jung, Gijung; Lee, Jun-Young; Sohn, Chul-Ho; Lee, Yun-Sang; Kim, Yu Kyeong; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Despite known associations between low blood hemoglobin level and Alzheimer’s disease (AD) or cognitive impairment, the underlying neuropathological links are poorly understood. We aimed to examine the relationships of blood hemoglobin levels with in vivo AD pathologies (i.e., cerebral beta-amyloid [A-beta] deposition, tau deposition, and AD-signature degeneration) and white matter hyperintensities (WMHs), which are a measure of cerebrovascular injury. We also investigated the association between hemoglobin level and cognitive performance, and then assessed whether such an association is mediated by brain pathologies. Methods: A total of 428 non-demented older adults underwent comprehensive clinical assessments, hemoglobin level measurement, and multimodal brain imaging, including Pittsburgh compound B-positron emission tomography (PET), AV-1451 PET, fluorodeoxyglucose (FDG)-PET, and magnetic resonance imaging. Episodic memory score and global cognition scores were also measured. Results: A lower hemoglobin level was significantly associated with reduced AD-signature cerebral glucose metabolism (AD-CM), but not A-beta deposition, tau deposition, or WMH volume. A lower hemoglobin level was also significantly associated with poorer episodic memory and global cognition scores, but such associations disappeared when AD-CM was controlled as a covariate, indicating that AD-CM has a moderating effect. Conclusion: The present findings suggest that low blood hemoglobin in older adults is associated with cognitive decline via reduced brain metabolism, which seems to be independent of those aspects of AD-specific protein pathologies and cerebrovascular injury that are reflected in PET and MRI measures.